Knowledge of basic life support among health care professionals in a tertiary care hospital in Chitradurga - Rajashekar, Somarouthu; M. R., Nagendra Gowda; Anthony, Ajith (International Journal Of Community Medicine And Public Health, 2018)
Background: Cardiovascular diseases are the major public health concern worldwide.Survival after cardiopulmonary arrest is usually low and depends on early intervention, quality of cardiopulmonary resuscitation (CPR) and time of initiation of defibrillation post cardiac arrest. Basic life support (BLS) is a key component of chain of survival. The aim of the study was to assess the knowledge of medical students, doctors, nursing students, nursing staff in Basic Life Support. Methods: A cross sectional study was conducted in Basaveshwara Medical College and Hospital. Those who were willing to participate in the study and who gave informed consent, were administered a self-filling written questionnaire. A total of 400 people were administered the questionnaire, out of which 388 filled the Performa completely. Results: This study was conducted to evaluate knowledge of basic life support among 388 health care professionals took part in the study of which 64.5% were medical students, 8.7% were doctors, 10.3% were nursing staff and 16.5% were nursing students. The study revealed that there is poor knowledge of basic life support among the respondents and 76% of them wanted basic life support to be included in the curriculum. Conclusions: Awareness and knowledge about basic life support is mandatory among health care professionals as they encounter such situation on a daily basis and will help them a long way in saving lives, thus knowledge in basic life support is very essential as health care professionals will get exposed to such situation more often.